MODULATING THE DRUG SOLUBILITY OF ACECLOFENAC BY DESIGN AS SOLID LIPID PARTICLES: IN VITRO/IN VIVO CORRELATION - ABDOUN, SIHAM A.; ALSUBAIYEL, AMAL M.; GABER, DALIA A.; ALSAUDI, BAYAN S.; ALRASHED, HAIFA A.; ALJARBOOA, NORAH F.; ALRADDADI, RANEEM H.; ALHARBI, RAZAN R.; MOHAMED, HEBA A. (International Journal of Applied Pharmaceutics, 2023)
Objective: The main objective of the study was to enhance the dissolution and hence the oral bioavailability of Aceclofenac (ACF). Methods: ACF was formulated as solid lipid particles (SLPs), which compressed into a tablet form for immediate release purpose and certain formulations were then coated by Eudragit RS100 polymer for sustained release action. SLPs of ACF were prepared by melt fusion method under the optimum conditions, using Compritol ATO 888 (Cr), Precirol ATO 5 (Pr), glyceryl monstearate, polyethylene glycols 4000, and Poloxamer 188 at different ratios SLP formulations were characterized for particle size, flow characteristics. The compressed tablets were identified in term of hardness, friability, content, moisture uptake, and in vitro release. Oral pharmacokinetics of the optimum tablet formulation and marketed tablet as reference were studied in rabbits. Results: SLP of acecloenac (ACF) showed accepted flowing properties, and the dissolution rate of the ACF from tablets was significantly enhanced compared to unprocessed drug. The results showed that about 45.5±2.5% of AC was released within 30 min from F1 while 12.7±4.5% was released from commercial AC tablets. The in vivo studies verified that the Cmax was 1.98±0.29, 2.10±0.33, and 4.83±86 µg/µl for the optimized immediate, sustained formula and commercial tablet, respectively. While the area under the curve from zero time to 24 h for the immediate and sustained release formula was 1.79, and 2.41 fold greater than the marketed formulation. Conclusion: The results showed that solid lipid particles under optimized conditions might be an efficient method for improving the solubility and hence the bioavailability of poorly soluble drugs likes ACF. The proper coating of the formula helps to achieve a convenient release of the drug.